High visual demand following theta burst stimulation modulates the effect on visual cortex excitability - Brückner, Sabrina; Kammer, Thomas (Frontiers in Human Neuroscience, 2015)
Modulatory effects of repetitive transcranial magnetic stimulation depend on the activity of the stimulated cortical area before, during, and even after application. In the present study we investigated the effects of theta burst stimulation on visual cortex excitability using phosphene thresholds. In a between-group design either continuous or intermittent theta burst stimulation was applied with 100% of individual phosphene threshold intensity. We varied visual demand following stimulation in form of high demand (acuity task) or low demand (looking at the wall). No change of phosphene thresholds was observed directly after theta burst stimulation. We found increased phosphene thresholds only if subjects had high visual demand following continuous theta burst stimulation. With low visual demand following stimulation no change of phosphene threshold was observed. Intermittent theta burst stimulation had no effect on visual cortex excitability at all. Since other studies showed increased phosphene thresholds following continuous theta burst stimulation using subthreshold intensities, our results highlight the importance of stimulation intensity applying theta burst stimulation to the visual cortex. Furthermore, the state of the neurons in the stimulated cortex area not only before but also following theta burst stimulation has an important influence on the effects of stimulation, making it necessary to scrupulously control for activity during the whole experimental session in a study.